Perinatal HPA axis regulation and offspring neuropsychiatric development: mechanisms, developmental trajectories, and clinical implications - Yanwei Guo; Jinyi Liu; Yaru Peng; Xiaofeng Li (Frontiers in Endocrinology, 2026)
Maternal hypothalamic–pituitary–adrenal (HPA) axis regulation forms part of the maternal–placental–foetal system through which prenatal environments may influence offspring developmental trajectories. During pregnancy, cortisol supports placental function and foetal maturation; however, its developmental significance depends on exposure timing, magnitude, and duration, placental glucocorticoid regulation, and foetal susceptibility. This narrative review synthesises evidence regarding maternal psychological distress, endogenous glucocorticoid regulation, placental glucocorticoid pathways, antenatal synthetic glucocorticoid exposure, and offspring neuropsychiatric development. Human studies indicate that maternal psychological distress and HPA-axis-related measures represent related but distinct dimensions of prenatal exposure. Associations have been reported between depressive and anxiety symptoms, maternal cortisol profiles, placental HSD11B2/11β-HSD2-related measures, and offspring glucocorticoid regulation. However, findings vary according to exposure definition, gestational timing, biological matrix, placental sampling, foetal sex, and covariate adjustment. Most evidence remains observational and does not establish a continuous causal pathway from maternal psychological distress through placental glucocorticoid dysregulation to later neurodevelopmental outcomes. Across foetal life, infancy, and childhood, studies have examined associations with stress-system regulation, cognitive and language development, emotional and behavioural functioning, and psychiatric vulnerability. Mechanistic research implicates epigenetic, immune-inflammatory, neurotrophic, cellular, and microbial pathways, although their mediating roles in humans remain incompletely established. Antenatal corticosteroids provide substantial neonatal benefits when clinically indicated for threatened preterm birth; current uncertainty mainly concerns potential long-term effects of repeated or additional exposure. Psychosocial and dietary interventions may improve maternal wellbeing and selected physiological outcomes, but whether these effects are mediated through cortisol regulation remains unclear. Future research should integrate repeated endocrine phenotyping, placental functional assessment, early-life developmental phenotyping, causal-inference approaches, multi-omics strategies, and longitudinal developmental follow-up to distinguish causal mechanisms from adaptation, confounding, and correlated biomarkers.